Dasatinib anhydrate containing oral formulation improves variability and bioavailability in humans - Hofmann, Jiří; Bartůněk, Aleš; Hauser, Tomáš; Sedmak, Gregor; Beránek, Josef; Ryšánek, Pavel; Šíma, Martin; Slanař, Ondřej (Leukemia, 2023)
Dasatinib monohydrate indicated for the treatment of chronic myeloid leukemia displays pH-dependent solubility. The aim of reported development program of novel dasatinib anhydrate containing formulation was to demonstrate improved absorption and lower pharmacokinetic variability compared to dasatinib monohydrate. In a bioavailability study comparing formulations containing 110.6 mg and 140 mg of dasatinib as anhydrate and monohydrate, respectively, both C max and AUC of dasatinib were within standard 80.00–125.00% range, while the intra- and inter-subject variability for AUC 0-inf after the test product was approximately 3-fold and 1.5-fold less than after the reference, respectively. In a drug–drug interaction study, omeprazole 40 mg reduced the mean AUC 0-inf of dasatinib by 19%, when the test was ingested 2 h before the 5th omeprazole dose. This decrease of exposure is clinically irrelevant and substantially less than after the reference. Co-prescription analysis supports the importance of pH-dependent solubility of dasatinib, as >21% of patients were treated concomitantly with a PPI and dasatinib despite warnings against this co-medication in the SmPC. The novel dasatinib anhydrate containing formulation demonstrated improved absorption and less pharmacokinetic variability compared to dasatinib monohydrate product, which may translate into improved clinical outcomes, although this needs to be proven by an appropriate trial.